A Discrete Wavelet Transform Based Approach for Enhancement of Lung Images - Archana J. N., Dr. Aishwarya P. (International Journal of Advanced Science and Technology, 2020)
Medical images captured using various imaging techniques and devices possess different levels of efficiency in terms of clarity. Contrast is the major parameter used to identify the quality in a medical image.The sharpness of such images need to be improved to focus on their critical differences so as to enhance superior visual display and increase their accuracy. Proposing a wavelet based algorithm to enhance the lung images is the aim of this paper. The proposed heuristic algorithm used here is by setting parameters forthreshold decomposition and the sharpness percentage.The performance metrics indicating the quality and efficiency based on Discrete Wavelet Transform (DWT) and the algorithm, along with the experimental results for a given lung image is illustrated.